2020
DOI: 10.1002/apj.2423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flue gas components on Hg0 oxidation and adsorption by modified walnut shell coke in O2/CO2 atmosphere

Abstract: Walnut shell was pyrolyzed and then impregnated with NH4Br to make sorbent for Hg0 removal. The effect of flue gas components on Hg0 removal performance was studied in O2/CO2 atmosphere, and the results were compared with those in O2/N2 atmosphere. The mercury valence distribution during adsorption was obtained. NH4Br‐modified walnut shell coke promoted Hg0 removal, the Br‐containing chemisorption site was a crucial factor. Although addition of CO2 did not introduce new oxygen‐containing functional groups or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…The N‐5 and N‐6 structures were gradually transformed into more stable N‐Q structures that had more aromatic ring. Wang 19 also obtained the experimental conclusions that the N‐5 and N‐6 structures on the surface of char samples decreased and the N‐Q increased as the reaction temperature increased during the temperature‐programmed reduction of NO experiments. Zhang 30 also conducted XPS analysis on char samples with two different pyrolysis temperatures and found that the relative contents of N‐5 and N‐6 on the surface of the pyrolysis char that prepared at 1000°C are lower than that at 800°C under high pressure (0.8–1.2 MPa) conditions, while the evolution trends of N‐Q of those were opposite.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The N‐5 and N‐6 structures were gradually transformed into more stable N‐Q structures that had more aromatic ring. Wang 19 also obtained the experimental conclusions that the N‐5 and N‐6 structures on the surface of char samples decreased and the N‐Q increased as the reaction temperature increased during the temperature‐programmed reduction of NO experiments. Zhang 30 also conducted XPS analysis on char samples with two different pyrolysis temperatures and found that the relative contents of N‐5 and N‐6 on the surface of the pyrolysis char that prepared at 1000°C are lower than that at 800°C under high pressure (0.8–1.2 MPa) conditions, while the evolution trends of N‐Q of those were opposite.…”
Section: Resultsmentioning
confidence: 92%
“…Its main components were NO, N 2 O, and NO 2 , of which NO accounted for more than 90%. At present, many researchers have carried out some studies on the NO x emission characteristics during the combustion process of pulverized coal/char samples under pressurized oxy‐fuel combustion conditions 8–19 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, significantly novel materials and processes have been developed to efficiently accomplish mercury removal from air and water at plant scale 9–13 . Furthermore, much research has been done to oxidize the mercury vapour from Hg 0 to Hg 2+ to blunt its detrimental consequences on lungs and brain after inhalation 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Furthermore, much research has been done to oxidize the mercury vapour from Hg 0 to Hg 2+ to blunt its detrimental consequences on lungs and brain after inhalation. [14][15][16] To overcome the drawback of graphite erosion, the present work employs tubular packing of stainless steel SS-304 with tungsten carbide (WC) coated on its outer surface using indigenously developed laser-directed energy deposition (LDED) technique for application as a plausible alternative to conventional graphite packing. Meneghini and Bertin observed that the coating on outer surface of amalgam wettable material (here, SS-304) should be pure or compound carbide of electrically conducting transition metals such as titanium, zirconium, niobium, tantalum or tungsten.…”
Section: Introductionmentioning
confidence: 99%